(untitled) - Tan, Ding Eing (Singapore, 1980)
1. The malacca sultanate, 2. The Malay power and The Portuguese, 3. The johore empire and foreign power: Maly and european
Keywords: Malaysia,Singapore,Malaysia,Singapore,Singapore; History,History,Lịch sử,Lịch sử,Lịch sử